Murilo Mendes,leitor de Romano Guardini1 - Simpson, Pablo [UNESP] (Instituto de Estudos Avançados da Universidade de São Paulo, 2020)
This paper presents and contextualizes the publication of an article by Murilo Mendes in 1948 titled “A Revolutionary Book”, on the book The Lord (Der Herr, 1937) by Italian-German theologian Romano Guardini. Starting with the study of personal libraries of religious writers, we intend to situate Mendes’ article in the context of the aesthetic and theological disputes in Brazilian Catholic thought, and understand how reading Guardini influenced Mendes’ poetry.

Este texto apresenta e contextualiza a publicação de um artigo de Murilo Mendes em 1948 com o título “Um livro revolucionário”, dedicado ao livro O Senhor (Der Herr, 1937) do teólogo ítalo-alemão Romano Guardini. Partindo do estudo das bibliotecas pessoais de escritores religiosos, pretende-se situar o artigo de Murilo Mendes no contexto das disputas estéticas e teológicas no pensamento católico brasileiro, tanto quanto compreender os desdobramentos da leitura de Guardini para a sua poética.
Keywords: Murilo Mendes; Romano Guardini; Brazilian poetry; Theology; Murilo Mendes; Romano Guardini; Poesia brasileira; Teologia